1998
DOI: 10.1183/09031936.98.11061301
|View full text |Cite
|
Sign up to set email alerts
|

Acid fog and hospital visits for asthma: an epidemiological study

Abstract: The aim of this study was to elucidate the adverse respiratory effects of naturally occurring acid fog. In total, 102 adult asthmatic patients (44 nonatopic and 58 atopic) were studied for a 2 yr period (January 1992 to December 1993) in Kushiro, a city with only a small industrial area, located in the northern-most island in Japan. Fog occurred on 378 out of 731 days, and the acidity of the fog ranged from pH 3.32 to 6.91 (mean pH 4.95). The association between hospital visits for asthma and meteorological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
(32 reference statements)
1
20
1
1
Order By: Relevance
“…Ito et al [18] early in 1990s observed that emergency asthma visits in large hospitals were more frequent when temperature and vapor pressure (recorded by local meteorological observatories) were high, and that the observation was reproducible in two cities of different geographical locations in Japan. Similarly, Tanaka et al [19] found that naturally occurring acid fog increased hospital visits of adult asthmatic patients and that the fog effects were more evident among non-atopic asthmatics than among atopic patients. They added that gaseous air pollutant levels were lower on foggy days than on fog-free days.…”
Section: Discussionmentioning
confidence: 91%
“…Ito et al [18] early in 1990s observed that emergency asthma visits in large hospitals were more frequent when temperature and vapor pressure (recorded by local meteorological observatories) were high, and that the observation was reproducible in two cities of different geographical locations in Japan. Similarly, Tanaka et al [19] found that naturally occurring acid fog increased hospital visits of adult asthmatic patients and that the fog effects were more evident among non-atopic asthmatics than among atopic patients. They added that gaseous air pollutant levels were lower on foggy days than on fog-free days.…”
Section: Discussionmentioning
confidence: 91%
“…ese activities are part of the core activities of modern societies, most notably aircraft operations, shipping [3], and road traffic [4]. Moreover, when the fog contains heavy pollutants, it is also harmful to human health [5]. is is why accurate forecasts of fog and haze have become an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollutants, such as nitrogen oxides ( NO x ), sulfur dioxides (SO 2 ), ozone (O 3 ), sulfuric acid (H 2 SO 4 ), and nitric acid (HNO 3 ), are among the constituents of acid fog; most of the fog acidity is attributable to the latter two [6]. The increase in respiratory mortality and morbidity, and of cardiopulmonary and lung cancer mortality is associated with exposure to fine aerial aerosol particles (in particular acidic ones), microbes, sulfur oxide and sulfur dioxide [6,7,100,101] (see Table 1).…”
Section: Impacts Of Fog On Human Healthmentioning
confidence: 99%
“…The increase in respiratory mortality and morbidity, and of cardiopulmonary and lung cancer mortality is associated with exposure to fine aerial aerosol particles (in particular acidic ones), microbes, sulfur oxide and sulfur dioxide [6,7,100,101] (see Table 1). Table 1.…”
Section: Impacts Of Fog On Human Healthmentioning
confidence: 99%
See 1 more Smart Citation